VD_FINDINFO HC / 2011 / 70 vom 11. Februar 2011 - VD Tribunal cantonal (2011)
DEMEURE, EXPULSION DE LOCATAIRE, LOI CANTONALE RELATIVE À LA PROCÉDURE EN MATIÈRE DE BAIL, DÉLAI | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 9 Cst., 23 al. 2 LPEBL, 23 LPEBL